Transparency and quality assessment of research data in post-Soviet area studies: The potential of an interactive online platform. Issue 2 (July 2019) - Heinrich, Andreas; Herrmann, Felix; Pleines, Heiko
The social sciences are increasingly addressing the quality of research data and debating ways to improve data transparency, that is, the availability of original research data to corroborate claims made in academic publications. This article offers a systematic discussion of related problems and challenges with the example of post-Soviet area studies. It goes on to examine ways to improve data transparency. Although the Internet has a huge potential for linking research with resulting publications and underlying data as well as for organizing a collective discussion around the research, current data repositories do not truly go beyond basic upload and download functions for datasets. With the example of the Discuss Data project, this article gives an overview of more elaborated features that can easily be implemented to improve the visibility and quality assessment of data collections. Finally, it discusses ethical concerns about data transparency related to privacy protection and copyrights.